2020
DOI: 10.1029/2020jc016120
|View full text |Cite
|
Sign up to set email alerts
|

Breaking of Internal Kelvin Waves Shoaling on a Slope

Abstract: In stratified flow, breaking of internal waves over slopes induces resuspension of bottom sediments and transport of mass. When internal waves shoal and break, flow dynamics and mass transport differ significantly according to whether the Coriolis force is included or neglected. Despite its importance, the currents generated by breaking internal Kelvin waves remain uninvestigated. Therefore, this study considers breaking of internal waves over a uniform slope under Coriolis with equivalent upper-and lower-laye… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…To estimate the residence time in YYL, we performed three‐dimensional hydrological simulations using a three‐dimensional environmental model, Fantom, which is based on object‐oriented programming methods (Laniak et al., 2013; Maruya et al., 2010; Nakamoto et al., 2013; Nakayama et al., 2014, 2016; Nakayama, Sato, et al., 2020; Nakayama, Shintani, et al., 2020). To evaluate bathymetry's effects on the flow field and residence time, we used a Fantom to simulate the bottom slope in a z coordinate system with partial cells (Adcroft, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…To estimate the residence time in YYL, we performed three‐dimensional hydrological simulations using a three‐dimensional environmental model, Fantom, which is based on object‐oriented programming methods (Laniak et al., 2013; Maruya et al., 2010; Nakamoto et al., 2013; Nakayama et al., 2014, 2016; Nakayama, Sato, et al., 2020; Nakayama, Shintani, et al., 2020). To evaluate bathymetry's effects on the flow field and residence time, we used a Fantom to simulate the bottom slope in a z coordinate system with partial cells (Adcroft, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we extend the above analysis to develop a spatially (horizontally) integrated DIC (SiDIC) numerical model suitable for shallow water areas, which is able to clarify the vertical and temporal changes of DIC. The base model is a three-dimensional environmental model, Fantom (Nakayama, Sato, et al, 2020;Nakayama et al, 2014Nakayama et al, , 2016. The governing equation is the Navier-Stokes equation, and object-oriented programming is used.…”
Section: A Dynamic Sidic Model Considering Savmentioning
confidence: 99%
“…(2009) have shown that much of the Earth’s carbon is captured and stored naturally as “blue carbon” in oceanic and coastal ecosystems, with vegetated habitats, such as mangroves and submerged aquatic vegetation (SAV), accounting for more than 50% of all carbon storage in ocean sediment. Previous studies have shown that SAV enhances the stratification of the water column (Nakayama, Sato, et al., 2020), suppressing vertical water exchange in shallow water areas (Ghisalberti & Nepf, 2006, 2009). When stratification occurs, large amounts of dissolved inorganic carbon (DIC) can accumulate in the deeper layers of an aquatic ecosystem because the dampening of vertical mixing prevents the flux of carbon between the upper and lower layers (Lin et al., 2021, 2022).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The tilting of the thermocline promotes mixing, specifically in the littoral zone (MacIntyre & Jellison, 2001), along with littoral‐pelagic mass exchange (Rao & Schwab, 2007). During relaxation, when upwelling winds weaken, complex phenomena characterize the nearshore area as internal waves may interact with lake morphometry, resulting in internal wave shoaling and breaking (Horn et al., 2001; Nakayama et al., 2020).…”
Section: Introductionmentioning
confidence: 99%